Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Certainly! Let's tackle the problem step-by-step.
### 1. Rewrite the Equation by Completing the Square
Given the equation:
[tex]\[ 6x + 55 = x^2 \][/tex]
First, rearrange it to the standard quadratic form:
[tex]\[ x^2 - 6x - 55 = 0 \][/tex]
To complete the square, we follow these steps:
a) Take the coefficient of the linear term (here, -6), halve it, and square the result:
[tex]\[ \left(\frac{-6}{2}\right)^2 = (-3)^2 = 9 \][/tex]
b) Add and subtract this square inside the equation:
[tex]\[ x^2 - 6x + 9 - 9 - 55 = 0 \][/tex]
c) Rearrange to group the perfect square trinomial:
[tex]\[ (x - 3)^2 - 9 - 55 = 0 \][/tex]
d) Simplify:
[tex]\[ (x - 3)^2 - 64 = 0 \][/tex]
e) Rewrite it into the completed square form:
[tex]\[ (x - 3)^2 = 64 \][/tex]
So, the equation in completed square form is:
[tex]\[ (x - 3)^2 = 64 \][/tex]
### 2. Solve the Equation
To find the solutions to the equation [tex]\((x - 3)^2 = 64\)[/tex], we need to take the square root of both sides:
[tex]\[ x - 3 = \pm \sqrt{64} \][/tex]
[tex]\[ x - 3 = \pm 8 \][/tex]
This gives us two possible solutions:
[tex]\[ x - 3 = 8 \Rightarrow x = 8 + 3 \Rightarrow x = 11 \][/tex]
[tex]\[ x - 3 = -8 \Rightarrow x = -8 + 3 \Rightarrow x = -5 \][/tex]
Thus, the solutions to the equation are:
[tex]\[ x = -5 \text{ and } x = 11 \][/tex]
Comparing these solutions with the given choices, they match the solutions in the format of:
(B) [tex]\( x = 3 \pm 8 \)[/tex]
where [tex]\(-5\)[/tex] corresponds to [tex]\(3 - 8\)[/tex] and [tex]\(11\)[/tex] corresponds to [tex]\(3 + 8\)[/tex].
Therefore, the correct answer is:
(B) [tex]\( x = 3 \pm 8 \)[/tex]
### 1. Rewrite the Equation by Completing the Square
Given the equation:
[tex]\[ 6x + 55 = x^2 \][/tex]
First, rearrange it to the standard quadratic form:
[tex]\[ x^2 - 6x - 55 = 0 \][/tex]
To complete the square, we follow these steps:
a) Take the coefficient of the linear term (here, -6), halve it, and square the result:
[tex]\[ \left(\frac{-6}{2}\right)^2 = (-3)^2 = 9 \][/tex]
b) Add and subtract this square inside the equation:
[tex]\[ x^2 - 6x + 9 - 9 - 55 = 0 \][/tex]
c) Rearrange to group the perfect square trinomial:
[tex]\[ (x - 3)^2 - 9 - 55 = 0 \][/tex]
d) Simplify:
[tex]\[ (x - 3)^2 - 64 = 0 \][/tex]
e) Rewrite it into the completed square form:
[tex]\[ (x - 3)^2 = 64 \][/tex]
So, the equation in completed square form is:
[tex]\[ (x - 3)^2 = 64 \][/tex]
### 2. Solve the Equation
To find the solutions to the equation [tex]\((x - 3)^2 = 64\)[/tex], we need to take the square root of both sides:
[tex]\[ x - 3 = \pm \sqrt{64} \][/tex]
[tex]\[ x - 3 = \pm 8 \][/tex]
This gives us two possible solutions:
[tex]\[ x - 3 = 8 \Rightarrow x = 8 + 3 \Rightarrow x = 11 \][/tex]
[tex]\[ x - 3 = -8 \Rightarrow x = -8 + 3 \Rightarrow x = -5 \][/tex]
Thus, the solutions to the equation are:
[tex]\[ x = -5 \text{ and } x = 11 \][/tex]
Comparing these solutions with the given choices, they match the solutions in the format of:
(B) [tex]\( x = 3 \pm 8 \)[/tex]
where [tex]\(-5\)[/tex] corresponds to [tex]\(3 - 8\)[/tex] and [tex]\(11\)[/tex] corresponds to [tex]\(3 + 8\)[/tex].
Therefore, the correct answer is:
(B) [tex]\( x = 3 \pm 8 \)[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.